2021
DOI: 10.46481/jnsps.2021.157
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Time induced Structural and Optical Properties of Lead Tin Sulphide Thin Films

Abstract: Lead tin sulphide (Pb-Sn-S) thin films (TFs) were deposited on fluorine-doped tin oxide (FTO) substrates via the electrochemical deposition process using lead (II) nitrate [Pb(NO3)2], tin (II) chloride dehydrate [SnCl2.2H2O] and thiacetamide [C2H5NS] precursors as sources of lead (Pb), tin (Sn) and sulphur (S). The solution of all the compounds was harmonized with a stirrer (magnetic) at 300k. In this study, we reported on the improvements in the properties (structural and optical) of Pb-Sn-S TFs by varying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It could also be a result of the increase in the period of deposition, which restructures the crystalline sizes and, thus, improves the transmittance of the deposited films, as indicated by the SEM studies. The elevated transmittance within the spectra range indicated in Figure 4 makes CZFS thin films a good conducting material for solar cells, pyro-electric detectors, and LED applications [ 4 , 21 ].
Figure 5 Transmittance spectrum of CZFS TFs.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also be a result of the increase in the period of deposition, which restructures the crystalline sizes and, thus, improves the transmittance of the deposited films, as indicated by the SEM studies. The elevated transmittance within the spectra range indicated in Figure 4 makes CZFS thin films a good conducting material for solar cells, pyro-electric detectors, and LED applications [ 4 , 21 ].
Figure 5 Transmittance spectrum of CZFS TFs.
…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the E g of the material tends to fall as the deposition period is increased, owing to growth in the crystalline sizes [ 18 ]. It is also suggested that the band trailing initiated by the disorder within the CZFS system of the films contributes significantly to the variations in the E g values [ 21 ]. Furthermore, the effects of impurities and defects, transition tail, shift effects, and residual strain all have a significant impact on the Eg of a semiconductor thin film system [ 13 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 shows the band gap of the PbSnS thin film. Generally, band gap energy in semiconducting materials is mostly influenced by their structural defects, crystallinity, impurities, grain sizes as well as grain boundary disorders [22]. Figure 8, reveals that the samples have direct band transition with an estimated band gap of 1.68 eV.…”
Section: Determination Of the Optical Band Gapmentioning
confidence: 99%
“…Interestingly, some authors had worked on this concept of corrugated boundaries and other related wave propagation phenomena [21][22][23][24][25][26][27][28][29]. Also, certain discussions on materials [30][31][32][33] could aid understanding of material characterizations.…”
Section: Introductionmentioning
confidence: 99%